2018
DOI: 10.5897/jphe2018.1000
|View full text |Cite
|
Sign up to set email alerts
|

Malaria outbreak and contracting factors in Afar Region, Ethiopia, 2016

Abstract: On July 5, 2016, Amibera District Health office was alerted of excess of malaria cases in two villages. Within July 5 to 17, 2016 malaria outbreak and associations factors were investigated. A malaria case is when a person with fever or fever with headache is confirmed either microscopically to have Plasmodium parasites or by Rapid Diagnostic Test (RDT) to detect the malaria antigens. In the last five years malaria data were reviewed from 2011 to 2015 at the district level. Cases were identified by using line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
1
2
0
Order By: Relevance
“…Similarly, our study recognized that people found close to the stagnant water were 3.3 times more affected than those who lived far from it. This finding is supported by a report from Afar, Ethiopia [19].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, our study recognized that people found close to the stagnant water were 3.3 times more affected than those who lived far from it. This finding is supported by a report from Afar, Ethiopia [19].…”
Section: Discussionsupporting
confidence: 90%
“…Malaria surveillance in endemic regions assists in reducing the burden of morbidity and mortality by providing data for trend analysis, resource allocation, vector control monitoring, drug efficacy and resistance and epidemic detection, preparedness and response [7]. Poor epidemic preparedness and response (EPR) can result in the inability to analyse and interpret surveillance data which leads to late notification and delayed outbreak investigation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Afar Region is characterized by the lowland areas (≤1500 m altitude) with hot or warm climate. This special geography and climate leads to malaria outbreak epidemics and high prevalence of malaria disease in Afar region [5]. Ethiopia is a home of diversified flora which have been widely used as traditional medicine.…”
Section: Introductionmentioning
confidence: 99%